Humusica 1, article 5: Terrestrial humus systems and forms — Keys of classification of humus systems and forms - Zanella, Augusto; Ponge, Jean-François; Jabiol, Bernard; Sartori, Giacomo; Kolb, Ekart; Le Bayon, Renée-Claire; Gobat, Jean-Michel; Aubert, Michaël; De Waal, Rein; Van Delft, Bas; Vacca, Andrea; Serra, Gianluca; et al. (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2018)
•One by one, the key for a classification of humus systems and forms in the field.•General environmental characters and distribution of humus systems.•Synthetic field key of classification of humus systems and forms. This article is an as simple as possible key of classification of terrestrial (aerobic, not submersed) topsoils (organic and organic-mineral series of soil horizons). Based on the introduction exposed in Humusica 1, article 1, and using vocabulary and definitions listed in article 4, a classification is proposed for better understanding the biological functioning of the soil, partially disclosing the process of litter digestion. Five types of terrestrial topsoils, called terrestrial humus systems, are described and illustrated with the help of photographs. Within each humus system, 3–4 humus forms are also revealed, corresponding to similar series of soil horizons generated in a relatively homogeneous environment whose range of ecological factors is not so large to overstep and cause the genesis of another different humus system. The article ends with a figure that shows the relationship between Tangel and Amphi humus systems, and a dichotomous key of classification that one can easily print and bring in the field for practicing humus classification.